Morphogenesis in guinea grass pastures under rotational grazing strategies - Montagner,Denise Baptaglin (2012)
This study was conducted in order to evaluate the morphogenetic and structural characteristics of guinea grass cv. Mombasa under three post-grazing heights (intense - 30 cm, lenient - 50 cm and variable - 50 in spring-summer and 30 cm in autumn-winter) when sward light interception reached 95% during regrowth. Post-grazing heights were allocated to experimental units (0.25 ha) in a completely randomized block design with three replications. Post-grazing heights affected only leaf elongation rate and the number of live leaves. Pastures managed with variable post-grazing height showed higher leaf elongation rate in the summer of 2007. This management strategy also resulted in a higher number of live leaves. During the spring of 2006, plants showed lower leaf elongation rate, leaf appearance rate and number of live leaves, and greater phyllochron and leaf lifespan. In contrast, during the summer of 2007, the leaf appearance rate, leaf elongation rate, number of live leaves, and final leaf length were greater while phyllochron, stem elongation rate, and leaf senescence rate were lower. The management of the guinea grass cv. Mombasa with intense or variable post-grazing height throughout the year seems to represent an interesting management target, in terms of leaf appearance rate and number of live leaves.